Post-silking leaf senescence is delayed in low-N-tolerant maize cultivars under low N fertilization - Gui Wei; Xinglong Wang; Yawei Wu; Fan Liu; Tianqiong Lan; Qinlin Liu; Chengcheng Lyu; Fanlei Kong; Jichao Yuan (Crop Journal)
A four-year field experiment was conducted with two cultivars and four N rate to investigate the spatio-temporal characteristics of leaf senescence in maize after silking and its response to N fertilizer rates on them, as well as to reveal the differences in post-silking chlorophyll degradation between low-N-tolerant cultivars. The results showed that the order of leaf senescence after silking in maize was lower leaf > upper leaf > ear leaf, leaf tip > middle > base. Increasing N fertilizer down-regulated the expression of ZmCLH2 and ZmPPH in the leaves at 10–30 d after silking, reducing CLH and PPH activities, thereby delaying the leaf senescence. These effects were more prominent in low-N-sensitive cultivar Xianyu 508 (XY508) than in low-N-tolerant cultivar Zhenghong 311 (ZH311), especially in the lower leaves and leaf tip. Under low N condition, leaf yellowing and chlorophyll degradation occurred later and slower in ZH311 than in XY508. This resulted in a higher post-silking dry matter accumulation and grain yield in ZH311, which may be one of the important physiological bases of low nitrogen tolerant cultivars. Future research should focus on developing low-N-tolerant maize cultivars with slower leaf senescence near the ear after silking.